Can voicing conflict within experiential learning groups facilitate connection? building and developing effective multi-disciplinary team-working skills. Issue 1 (2nd January 2017) - Keville, Saskia; Conlan, Louise-Margaret; Adlington, Becky; Brindley, Rob; Abraham-Smith, Kelly; Shaverin, Lisa; Simpson, Leon; Nel, Pieter W.
Abstract: In the UK, Clinical Psychologists (CPs) work in a variety of settings within the National Health Service (NHS), often within Multi-Disciplinary Teams (MDTs). Problem-Based Learning (PBL) within CP training at the University of Hertfordshire (UH) offers unique opportunities to combine scientist-practitioner and reflective-practitioner models to learn about group dynamics from the personal experience of working within an experiential learning group. Further, given Trainees work three days per week on placement within MDTs in the NHS, the learning gained within a 'safer' PBL context can be utilised within these clinical settings. For two years, Trainees at UH have to work in small PBL groups with five or six members learning to work together to achieve a goal (four assessed presentations) negotiating their own personal and professional journey, as well as a group journey. Consequently, PBL offers trainees opportunities to learn (1) how individuals work within a group; (2) how personal experiences influence this process; (3) how others influence them and are influenced by them; and (4) how a group of diverse individuals conceptualise, understand and convey case vignettes to an audience. Within these groups, many Trainees learn to speak out, reflect, listen attentively, empathise, validate and accept diverse experiences. Further, when differences dominate they often learn to negotiate these, finding a way to maintain effective team working in order to complete the presentation. Focusing on the conflict that can occur within (any) group, this paper explores themes from the reflective narratives of six trainees: parallels and differences between MDTs and PBL groups, striving for and achieving authenticity; and conflict as a 'swear' word. We conclude that exploring the role PBL can play in training individuals to work effectively in teams may be of benefit within the training of other professional groups.